2019
DOI: 10.1136/bmjopen-2019-032627
|View full text |Cite
|
Sign up to set email alerts
|

The Garmin-RUNSAFE Running Health Study on the aetiology of running-related injuries: rationale and design of an 18-month prospective cohort study including runners worldwide

Abstract: IntroductionRunning injuries affect millions of persons every year and have become a substantial public health issue owing to the popularity of running. To ensure adherence to running, it is important to prevent injuries and to have an in-depth understanding of the aetiology of running injuries. The main purpose of the present paper was to describe the design of a future prospective cohort study exploring if a dose–response relationship exists between changes in training load and running injury occurrence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…In collaboration with Garmin, RUNSAFE has launched a worldwide study recruiting runners willing to monitor their running habits with a Garmin device and report their injury and health status on a weekly basis over an 18-month period. With other big data, the relationship between running activity, personal characteristics, and risk of running-related injuries will be investigated (Nielsen et al 2019). This data source is fundamental for BERTHA, as the fitness data will be combined with air pollution data to investigate if physical activity in polluted areas increases the risk of heart-rate variability as a sign of effects of air quality on the cardiovascular system.…”
Section: Physical Activitymentioning
confidence: 99%
“…In collaboration with Garmin, RUNSAFE has launched a worldwide study recruiting runners willing to monitor their running habits with a Garmin device and report their injury and health status on a weekly basis over an 18-month period. With other big data, the relationship between running activity, personal characteristics, and risk of running-related injuries will be investigated (Nielsen et al 2019). This data source is fundamental for BERTHA, as the fitness data will be combined with air pollution data to investigate if physical activity in polluted areas increases the risk of heart-rate variability as a sign of effects of air quality on the cardiovascular system.…”
Section: Physical Activitymentioning
confidence: 99%
“…The ability of wearable devices to capture massive sample sizes in running epidemiology studies will bolster statistical power in future studies to provide insight into less common and poorly understood running-related injuries, such as femoral stress fractures(4). One such ongoing study aims to collect data from 20,000 runners by combining self-reported injury data and running metrics captured by each runner's accelerometer-equipped GPS running watch (46).…”
Section: Injury Perspective Of External Training Loadmentioning
confidence: 99%
“…These conditions and running-related injury, in general, are major obstacles to exercise activity [5], so prevention of patellar and Achilles tendon injuries are important. In-depth knowledge about forces applied to the involved anatomical structures is needed because an injury occurs when the cumulative tendon load exceeds the structure's capacity to withstand the load [6][7][8]. Cumulative tendon load is considered a superior metric for the prediction of injury compared to running distance [9], which has been widely used in the previous literature [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a computationally simple algorithm to predict the cumulative force in the Achilles or the patellar tendon is an important step to improving the understanding of the etiology underpinning running injury in these structures. If successful, such algorithms can be used to obtain sessionspecific and structure-specific approximations of tissue loads in large-scale epidemiological studies examining the "too much training load, too soon"-theory [7]. Large-scale studies are needed to assess changes in the tendon force in different groups displaying different recovery patterns [7], running experience [6], previous injuries [6], and pain sensitivity [12], to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation